Comparison of pre training and post training knowledge of hypertension among medical officers of Narmada district of Gujarat, India - Asher, Archana D.; Godbole, Varsha Y.; Mehta, Kedar G. (International Journal of Advances in Medicine, 2019)
Background: Hypertension is a major risk factor contributing to cardiovascular and cerebrovascular diseases and death. Medical officers play an important role in Indian public health care system. The objective of this study was to evaluate the impact of training program on knowledge about hypertension among medical officers working in government health centres in Gujarat, India. Methods: A one day training program was conducted for medical officers of various Primary Health Centres (PHCs) and Community Health Centres (CHCs) in Narmada district of Gujarat. This training focussed on screening, diagnosis and management of hypertension, essential and secondary hypertension, lifestyle modifications, various anti-hypertensive drugs and practical aspects of examining a patient with hypertension. Impact of the training program was evaluated by a questionnaire consisting of 10 questions which was used as a pre-test and a post-test. Results: A total of 30 medical officers (18 male and 12 female) attended the training. The mean age of participants was 37.4 years and average clinical experience was 11 years. The pre-test mean score of participants was 4.52 and post-test mean score was 8.44. This improvement in the post-test mean score was found to be statistically significant. On comparison of questions answered incorrectly in pre-test and post-test, we found that there was a significant reduction in the number of questions answered incorrectly in the post-test. Conclusion: There was a significant improvement in the knowledge of medical officers regarding screening, diagnosis and management of hypertension as a result of their training.